Characterization of the scintillation time response of liquid argon detectors for dark matter search. (19th November 2021) - Agnes, P.; De Cecco, S.; Fan, A.; Fiorillo, G.; Franco, D.; Galbiati, C.; Giganti, C.; Korga, G.; Lebois, M.; Mandarano, A.; Martoff, C.J.; Pagani, L.; et al.
Abstract: The scintillation time response of liquid argon has a key role in the discrimination of electronic backgrounds in dark matter search experiments. However, its extraordinary rejection power can be affected by various detector effects such as the delayed light emission of TetraPhenyl Butadiene, the most commonly used wavelength shifter, and the electric drift field applied in Time Projection Chambers. In this work, we characterized the TetraPhenyl Butadiene delayed response and the dependence of the pulse shape discrimination on the electric field, exploiting the data acquired with the ARIS, a small-scale single-phase liquid argon detector exposed to monochromatic neutron and gamma sources at the ALTO facility of IJC Lab in Orsay.